Green Accounting Practices in Philippine Higher Education: A Mixed-Method Case Study of Institutional Readiness at a Local Government College - Margareth D. Asis; Francis Mae C. Edpalina; Alheigne Kyle C. Naguiat; Christian Albert E. Padilla; Kyle C. Panganiban; Ediric D. Gadia (Future Science / FSH-PH Publications, 2026)
Green Accounting promotes environmental accountability; however, there is a lack of empirical evidence on the application of Green Accounting in higher education institutions in developing economies, particularly in the Philippines. This study aimed to find out the level of preparedness of the institution for Green Accounting by examining their operational practices, stakeholder awareness, and the factors that affect the institution. The researchers used a convergent mixed-method for this study that combined quantitative and qualitative data. A checklist was distributed and answered by 102 respondents to gather quantitative data and 55 students and staff were interviewed to gather qualitative data using purposive sampling to have a diverse group of respondents to collect their perspectives on sustainability regarding their own awareness, perceptions, and experiences. The results show that Green Accounting implementation is still in its early stage or just getting started on its implementation. Numerous environmental practices remain in the “In-Progress” category. Waste reduction and management rank highest, followed by energy efficiency and water conservation. The implementation results range from 2.12 and 2.14. Most of the actions do not require large funding and depend on people’s behavior. However, activities that require significant financial investment, such as renewable energy, are still in the “Not Yet Started” stage due to financial and facility constraints. Despite positive developments like low or no-cost sustainability practices, the institution lacks data tracking and does not have the procedures needed for effective Green Accounting. Interviews indicate that the perceived technical difficulty of formal Green Accounting discourages its implementation.